GROWTH INHIBITION OF PATHOGENIC ROOT FUNGI BY EXTRACTS OF ECTOMYCORRHIZAL FUNGI OR Picea glehnii INOCULATED WITH ECTOMYCORRHIZAL FUNGI* - MARIA CATARINA MEGUMI KASUYA (BIOTROPIA, 1996)
This work sought to verify the presence of compounds with antimicrobial properties in extracts of ectomycorrhizal fungi or in Picea glehnii inoculated with ectomycorrhizal fungi. Extracts from Pisolithus tinctorius, Scleroderma flavidum, Amanita pantherina and Paxillus sp., grown in liquid culture media, and from P. glehnii seedlings inoculated or not with the above ectomycorrhizal fungi and cultivated in in vitro condition, were processed to obtain two fractions, water and ethyl acetate solubles. These fractions were tested for the presence of inhibitory constituents against Fusarium roseum, Pythium sp. and Rhizoctonia solani. Direct bioautography technique on TLC or paper disc technique was used, depending on the extract and pathogenic fungi tested. The results showed the production on inhibitory components, not only by ectomycorrhizal fungi, but also by P. glehnii inoculated or not with ectomycorrhizal fungi. The sensitivity varied considerably according to the type of fungus or extract. Key words: Japan/Mycorrhizas/Inh|bition/Extracts/Antimicrobial compounds/Amanita pantherina/Pisolithustinctorius/Paxillvs spJScleroderma flavidum/Fusarium roseum/Pythium spJRhizoctonia solani.